Sotsialni naslidky vymushenoi migratsii v Ukraini: ryzyky marginalizatsii ta sotsialnoi ekskliuzii [in Ukrainian] - Kuznetsova, I; Mikheieva, O; Gulyieva, G; Dragneva, R; Mykhnenko, V (Zenodo, 2018)
A policy brief based on an interdisciplinary study of social consequences of forced population displacement in Ukraine (2016-2018) [In Ukrainian]